2019
DOI: 10.1159/000500619
|View full text |Cite
|
Sign up to set email alerts
|

A 46,XY Female with a 9p24.3p24.1 Deletion and a 8q24.11q24.3 Duplication: A Case Report and Review of the Literature

Abstract: Deletion of distal 9p is associated with a rare clinical condition characterized by dysmorphic features, developmental delay, and ambiguous genitalia. The phenotype shows variable expressivity and is related to the size of the deletion. 8q24 duplication has been reported in only few cases to date, all showing dysmorphic features and mild psychomotor developmental delay. A case of chromosomal aberration involving a 9p terminal deletion with an 8q duplication has never been reported. Here, we describe a child wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Among these, TAF2(OMIM: 604912), KCNK9(OMIM: 605847), TRAPPC9(OMIM: 611966), and RECQL4 (OMIM: 603780) have been linked to the intellectual disability, while other genes such as SAMD12(OMIM: 618073), KCNQ3(OMIM: 602232) and GPAA1(OMIM: 603048)have been associated with epilepsy. 9,10 Hence, we speculate that the various malformations of the fetus in ultrasound may be mainly the result of distal deletion in 13q, among which, the cerebellar vermis hypoplasia is a severe abnormality. The 13q terminal deletion is mainly characterized by intellectual disability, developmental delay and congenital anomalies of the brain, such as Dandy-Walker malformation (DWM), corpus callosum agenesis, encephalocele and holoprosencephaly; facial deformity and other disorders, such as bowel atresia and lung hypoplasia.…”
Section: Discussionmentioning
confidence: 93%
“…Among these, TAF2(OMIM: 604912), KCNK9(OMIM: 605847), TRAPPC9(OMIM: 611966), and RECQL4 (OMIM: 603780) have been linked to the intellectual disability, while other genes such as SAMD12(OMIM: 618073), KCNQ3(OMIM: 602232) and GPAA1(OMIM: 603048)have been associated with epilepsy. 9,10 Hence, we speculate that the various malformations of the fetus in ultrasound may be mainly the result of distal deletion in 13q, among which, the cerebellar vermis hypoplasia is a severe abnormality. The 13q terminal deletion is mainly characterized by intellectual disability, developmental delay and congenital anomalies of the brain, such as Dandy-Walker malformation (DWM), corpus callosum agenesis, encephalocele and holoprosencephaly; facial deformity and other disorders, such as bowel atresia and lung hypoplasia.…”
Section: Discussionmentioning
confidence: 93%
“…ID is caused by perturbations in the significant biological functions that impact cellular networks present in different regions of the CNS. We identified the influence of each of the 44 prioritized genes ( Supplementary Table S5 ) in different tissues and found that these genes are mainly expressed in the CNS when compared with other tissues in humans ( Figure 3 ) [ 14 , 16 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, six genes from the duplicated region 18p11.32-p11.21 are highly expressed in several regions of the CNS, from which three of them (LAMA1, MYOM1, and TGIF1) were duplicated in individuals with ID [ 18 , 19 , 20 ]. Furthermore, patients with duplication of 8q24.13q24.3 region involving the KCNQ3, PTK2, ASAP1, and NDRG1 genes, which are widely expressed in CNS, presented ID [ 14 , 16 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Genomic data were collected from the literature where approximate breakpoints are known for 53 individuals with 9p deletion and duplication syndromes. 12 , 14 , 15 , 16 , 17 , 19 , 27 , 29 , 30 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 …”
Section: Methodsmentioning
confidence: 99%
“… 12 An important phenotype to note that often occurs in individuals with a 9p deletion is sex reversal and other differences in sex development (DSDs). 8 , 12 , 13 , 17 , 24 , 25 , 26 , 27 , 28 , 29 , 30 Ambiguous genitalia are estimated to be present in up to 70% of individuals with 9p deletion. 27 The 46,XY sex reversal phenotype is more commonly found in individuals with terminal 9p deletions than in those with more proximal deletions.…”
Section: Introductionmentioning
confidence: 99%